Homophobia, hate crime and men’s professional football - Humphries, Connor (Hate crime in football, 2023)
This chapter focuses on English men’s professional football, which has traditionally been a hostile environment for sexual minorities. Gay male footballers, or even those suspected of being gay, have been excluded, marginalized and subordinated from the game by men attempting to (re)prove and (re)establish their heteromasculinity. Over the past two decades, however, attitudes towards homosexuality have seen a marked improvement in the United Kingdom and, indeed, across much of the Western world. While there remain claims that sport – and men’s football in particular – is slower to adopt social change, a significant body of research has documented how football is becoming increasingly acceptant and inclusive of homosexuality. In this chapter, we outline some of this research before examining some of the ongoing issues with respect to homophobia in the professional game – paying particular attention to Kick It Out’s annual reporting statistics, which include reports of discrimination based on homophobia, biphobia and transphobia.